Rules and risk in the euro area - Anna Iara; Guntram B. Wolff (Bruegel, 2011)
With a unique data set summarizing the quality of rules-based fiscal governance in EU member states, we show that stronger fiscal rules in euro area members reduce sovereign risk premia, in particular in times of market stress. To do so, we develop a model of sovereign spreads that are determined by the probability of default in interaction with the level of risk aversion. Estimation of the model con firms the central predictions. The legal base of the rules and their enforcement mechanisms are the most important dimensions of rules-based fiscal governance.
Keywords: E43; E62; G12; H60; H63; 330; fiscal governance; numerical fiscal rules; sovereign spreads; sovereign risk; euro area; Finanzpolitik; Regelbindung; Länderrisiko; Öffentliche Anleihe; Eurozone; EU-Staaten